DREPTUL ANTIDISCRIMINATORIU ÎN CONTEXTUL INTERNAȚIONAL SI EUROPEAN, MĂSURI DE COMBATERE A DISCRIMINĂRII (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
The Anti-discrimination Law in The European and International Context, Actions to Fight Discrimination.When we discuss about the anti-discrimination law, we refer to the norms, national laws, conventions and treaties, as well as linking criteria and conflicts amongst them, that affirm and implement the principle of equality and non-discrimination. The anti-discrimination law at international and European level has evolved and continues to grow in order to cover the factors that cause and facilitate discrimination. Throughout the years, the legislation, the case law and adjustments within the treaties have consolidated its applicability. Each government is compelled to prevent any form of discrimination against men or women, implementing the gender quality principle. Moreover, the regulations issued by the European Directives and the documents comprising the norms, standards and policies have recently indicated a procedural system that massively relies on the scientific research and development, which contributes substantially to the fight against discrimination.